2022
DOI: 10.1002/app.52507
|View full text |Cite
|
Sign up to set email alerts
|

Development of optimal polymeric foams with superior sound absorption and transmission loss

Abstract: The objective of the current research is to propose new polymer composites with optimal acoustic properties. To do so, the ethylene‐vinyl acetate foam is employed as the based polymer and the nano silica, nano clay and graphene nanoplatelets are used as extra ingredients. The appropriate amounts of the blowing agent and nano materials are determined using the Taguchi design technique. Using the L9(34) Taguchi array, different foams are manufactured and their specifications are determined experimentally. Most i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Compared with metal foams, polymers, and their composite foams have the merits of lightweight and good corrosion resistance [29][30][31]. Mohammad et al [32] prepared vinyl-vinyl acetate composite foams lled with nano-silica, nano-clay, and graphene nanosheets through the method of uniform mixing, blow molding, and hot pressing. The ethylene vinyl acetate composite foams showed the best sound absorption performance with a noise reduction coe cient of 0.225 at a dosage of 2 phr for both silica and nano-clay and 0.2 phr for graphene nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with metal foams, polymers, and their composite foams have the merits of lightweight and good corrosion resistance [29][30][31]. Mohammad et al [32] prepared vinyl-vinyl acetate composite foams lled with nano-silica, nano-clay, and graphene nanosheets through the method of uniform mixing, blow molding, and hot pressing. The ethylene vinyl acetate composite foams showed the best sound absorption performance with a noise reduction coe cient of 0.225 at a dosage of 2 phr for both silica and nano-clay and 0.2 phr for graphene nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…They observed a SAC of 0.99 at 1.99 kHz frequency for 15 wt% fiber reinforcement. Nourmohammadi et al 36 presented the SA of different ethylene‐based foam samples and observed that adding multiple nanomaterials in polymeric foam samples enhanced the SAC.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with metal foams, polymers, and their composite foams have the merits of lightweight and good corrosion resistance [29][30][31]. Mohammad et al [32] prepared vinyl-vinyl acetate composite foams lled with nano-silica, nano-clay, and graphene nanosheets through the method of uniform mixing, blow molding, and hot pressing. The ethylene vinyl acetate composite foams showed the best sound absorption performance with a noise reduction coe cient of 0.225 at a dosage of 2 phr for both silica and nano-clay and 0.2 phr for graphene nanosheets.…”
Section: Introductionmentioning
confidence: 99%